Building for eternity : the history and technology of Roman concrete engineering in the sea - Brandon, C. J. (Christopher J.); Hohlfelder, Robert L.; Jackson, M. D.; Oleson, John Peter (Oxbow Books, 2014)
"This book explains how the Romans built so successfully in the sea with maritime concrete. The story is a mix of archaeological, geological, historical and chemical research, with relevance to both ancient and modern technology. It also bridges the gap between science and the humanities by integrating analytical materials science, history, and archaeology, along with underwater exploration. The book will be of interest to anyone interested in Roman architecture and engineering, and it will hold special interest for geologists and mineralogists studying the material characteristics of pyroclastic volcanic rocks and their alteration in seawater brines. The demonstrable durability and longevity of Roman maritime concrete structures may be of special interest to engineers working on cementing materials appropriate for the long-term storage of hazardous substances such as radioactive waste"--Provided by publisher.